Hydrogenation of the model object in the presence of nanocatalysts - Fengyun, М.; Xintai, S.; Tateyeva, A.B.; Akhmetkarimova, Zh.S.; Balabekova, D.A.; Berzhanova, R.S.; Meyramov, M.G. (Изд-во КарГУ, 2013)
The catalytic hydrogenation of the model object anthracene was presented in the article. The selection of conditions for the proceeding of the process was conducted. Hydrogenation process was carried out using nanocatalysts β-FeOOH, Fe(OA)3 and Fe3O4 in the ratio of 1 % in the presence of hydrogen. The effect of ini- tial hydrogen pressure on the yield of the products during the reaction was detected. The most effective additive for the catalytic hydrogenation of the model object anthracene was determined.
Keywords: catalytic hydrogenation; anthracene; nanocatalysts; polynuclear aromatic hydrocarbons; hydrocarbon feedstock; effective additive; model objects